2010
DOI: 10.1016/j.bbalip.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Limited cholesterol depletion causes aggregation of plasma membrane lipid rafts inducing T cell activation

Abstract: Acute cholesterol depletion is generally associated with decreased or abolished T cell signalling but it can also cause T cell activation. This anomaly has been addressed in Jurkat T cells using progressive cholesterol depletion with methyl--beta--cyclodextrin (MBCD). At depletion levels higher than 50% there is substantial cell death, which explains reports of signalling inhibition. At 10--20% depletion levels, tyrosine phosphorylation is increased, ERK is activated and there is a small increase in cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 64 publications
3
52
0
Order By: Relevance
“…We reconstituted the fluorescent FITC-LW21 at 3 mol% into C24∶1 PC GUVs and infused cholesterol by a recently developed MBCD-Chol exchange protocol. This allowed careful loading of membranes below saturation levels (23). Using confocal microscopy we observed the segregation of FITC-LW21 into microscaled, line-shaped domains within a fluid bilayer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We reconstituted the fluorescent FITC-LW21 at 3 mol% into C24∶1 PC GUVs and infused cholesterol by a recently developed MBCD-Chol exchange protocol. This allowed careful loading of membranes below saturation levels (23). Using confocal microscopy we observed the segregation of FITC-LW21 into microscaled, line-shaped domains within a fluid bilayer.…”
Section: Discussionmentioning
confidence: 97%
“…We always maintained 10 mol% of C18∶1 PC to keep the bilayer fluid and more stable (see SI Text). Then we carefully infused 3.8 μM cholesterol as a methyl-β-cyclodextrin complex (MBCD-Chol) (23). This induced a substantial clustering of FITC-LW21 in the C24∶1 PC membrane into line-shaped domains within minutes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Once a cell is dead, it is hardly surprising that a cellular process ceases to function and it is incorrect to ascribe this failure to the importance of cholesterol and/or lipid rafts. This was the case in the T cell signalling field [22] and care must be taken to make sure that cells remain viable. …”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work is therefore to understand the composition and more importantly, the initiation process of the formation of lipid rafts in cellular membranes. Prior studies have suggested the existence of interactions between cholesterol and sphingolipids (9). As cholesterol binds in-between two sphingomyelin molecules the assembly is rigid and more resistant to solvation, hence an increase in sphingolipids and a minimum amount of cholesterol may lead to lipid raft formation.…”
Section: Resultsmentioning
confidence: 99%